Optimal seismic retrofitting of reinforced concrete buildings by steel-jacketing using a genetic algorithm-based framework. (15th September 2020) - Di Trapani, Fabio; Malavisi, Marzia; Marano, Giuseppe Carlo; Sberna, Antonio Pio; Greco, Rita
Highlights: An new framework for the optimization of steel jacketing retrofitting interventions on RC columns is presented. The method can provide topological optimization (location) and amount of steel-jacketing reinforcement. The optimization process is based on a genetic algorithm handling a fiber-section model realized in OpenSees. The feasibility individual solutions is controlled by the capacity/demand ratio resulting from pushover analysis. The application of the method can effectively reduce retrofitting costs maintaining a specified safety level. The framework can be used by practitioners as a tool for sustainable retrofitting interventions. Abstract: Retrofitting of existing reinforced concrete (RC) frame structures by steel angles and battens (steel-jacketing) is a commonly employed technique used to retrofit beams and columns against gravity and seismic loads. Steel-jacketing (SJ) effectively provides additional deformation and strength capacity to RC members but its application is associated with noticeable downtime of the building and non-negligible costs, depending on the amount of structural and non-structural manufacturing and materials. This paper presents an optimization framework aimed at the minimization of seismic retrofitting-related costs by an optimal placement (topological optimization) and amount of steel-jacketing reinforcement. In the proposed framework a 3D RC frame fiber-section model implemented in OpenSees is handled by a genetic algorithm routine that iterates reinforcement configurations to match the optimal solution. The feasibility of each solution is controlled by the outcomes of a static pushover analysis in the framework of N2 method. Results will provide optimized location and amount of steel-jacketing reinforcement, showing how effective and sustainable reduction of retrofitting costs is achievable maintaining a specified safety level.